2007
DOI: 10.1039/b705460b
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the diffraction limit: far-field fluorescence imaging with ultrahigh resolution

Abstract: Fluorescence microscopy is an important and extensively utilised tool for imaging biological systems. However, the image resolution that can be obtained has a limit as defined through the laws of diffraction. Demand for improved resolution has stimulated research into developing methods to image beyond the diffraction limit based on far-field fluorescence microscopy techniques. Rapid progress is being made in this area of science with methods emerging that enable fluorescence imaging in the far-field to posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 75 publications
(210 reference statements)
0
34
0
Order By: Relevance
“…[22][23][24][25][26][27][28] Briefly, when incident pulses were tuned to a vibrational resonance of the cells or TBOGNPs the infrared light absorbed was proportional to the materials' absorption coefficients at the excitation wavelength, causing thermal heating which relaxed mechanically via expansion of the surface. 23 This deformation of the surface causes deflection of the mechanical probe in contact mode, which relaxes back according to a one end fixed-cantilever solution to the EulerBernoulli equation.…”
Section: Afm-ir Methodologymentioning
confidence: 99%
“…[22][23][24][25][26][27][28] Briefly, when incident pulses were tuned to a vibrational resonance of the cells or TBOGNPs the infrared light absorbed was proportional to the materials' absorption coefficients at the excitation wavelength, causing thermal heating which relaxed mechanically via expansion of the surface. 23 This deformation of the surface causes deflection of the mechanical probe in contact mode, which relaxes back according to a one end fixed-cantilever solution to the EulerBernoulli equation.…”
Section: Afm-ir Methodologymentioning
confidence: 99%
“…While the association between lipids and proteins within these microdomains directly affects biological functions and dynamic cell processes, their relationship is poorly understood in part due to the current limitations on nanoscale localization of membrane features [3]. Research into this topic has suggested that lipid rafts are involved, with diameters from 20-100 nm, a range which makes their direct visualization challenging using conventional microscopy [4]. Hinterdorfer et al [2] note the importance of plasma membrane heterogeneity for function as any factor that influences the structure of a cell can also alter its mechanical and chemical properties [5].…”
Section: Introductionmentioning
confidence: 99%
“…When probing small features such as viruses within a host organism [21], the power of the method for discriminating heterogeneous chemical signals far below the optical diffraction limit becomes apparent. ) present in the spectral derivative (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in new techniques for sub-diffraction imaging have been made for fluorescence based imaging. A number of fluorescence microscopy techniques have been developed to which overcome this limit in image resolution such as STED and PALM, and are increasingly applied to image both functional materials and biosystems [12]. While these methods are currently among the state-of-the-art methods for sub-diffraction optical imaging in common with other fluorescence methods these methods address specific fluorophore groups and are unable to detect non-luminescent materials present within a host system.…”
Section: Introductionmentioning
confidence: 99%